Central Planning in the Netherlands - Tinbergen, J. (Review of Economic Studies, 1947)
Journal Article Central Planning in the Netherlands Get access J. Tinbergen J. Tinbergen The Hague, Holland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 2, 1947, Pages 70–77, https://doi.org/10.2307/2295994 Published: 01 September 1947